Baseline Nutritional Status of Mother-Child Dyads in Urban Slums: Pre-Intervention Analysis for a Nutrition Informatics Intervention - Thakur, Shyamli; Bhargava, Samir; Gauniyal, Mansi (National Journal of Community Medicine, 2025)
Background: Urban slums are critical for public health intervention due to high population density, poor living conditions, and limited healthcare access. This study examines baseline nutritional and lifestyle patterns among mother-child dyads in the urban slums of Uttar Pradesh. The dyads were recruited for Nutritional Assessment and Intervention Kiosk (NAIK), a Population Health Informatics platform to address double burden of malnutrition. Methodology: This cross-sectional, pre-intervention study involved 406 mother-child dyads with children aged 2-5 years. Data on socio-demographic variables, anthropometric measurements, nutrient intake and lifestyle patterns were collected. Descriptive statistics summarized baseline characteristics. Results: The demographic profile showed predominantly low-income mothers with 43.34% without primary education. The mean ages of mothers and children were 33.98 ± 5.9 years and 46.91 ± 10.89 months, respectively. The waist-to-hip ratio was 0.92 ± 0.76 indicating cardiovascular risk factors with significant maternal obesity (47.78%). Education of the mother was found to be significantly associated with Mid Upper Arm Circumference (MUAC) of the child. The findings highlight the overnutrition in mothers and nutrient inadequacy in children, influenced by inadequate dietary intake and unhealthy lifestyle. Conclusions: This paper will comprehensively overview baseline population status, setting the stage for further analysis and evaluation of the intervention.